The Effect of Early Nutrition on Growth in Extremely Low Gestational Age Infants - Hiltunen, Henni (fi=Turun yliopisto|en=University of Turku|, 2016)
Objective: Extremely preterm birth is associated with high risk of extra-uterine growth retardation. We investigated whether nutritional management during the first seven days of life affects growth patterns until the corrected age of two years in extremely preterm infants. Methods: A retrospective study of 78 extremely preterm (<28 weeks of gestation) neonates was conducted. Data regarding parenteral and enteral intake of energy, protein, lipids and glucose during the first seven days of life were collected from patient records. The outcome measures included weight, height and head circumference with Z-scores at term-equivalent age and the corrected ages of one and two years. Analyses were performed with hierarchical linear mixed models. Results: Intake of energy during the first seven days of life was statistically significantly associated with weight, length and head circumference until the corrected age of two years after adjusting for potential confounding factors. Similar statistically significant associations were observed with lipid intake and weight and length but not with head circumference. Early intake of protein or glucose was not associated with growth parameters during the first two years of life. Conclusions: Energy intake during the first seven days of life tends to program the growth pattern throughout infancy. On the macronutrient level, early lipid intake was associated with subsequent growth, whereas early intake of protein or glucose was not. These results provide support for aggressive early nutritional management of extremely preterm infants.